Peci dan Politik: Simbol Keislaman dalam Lintasan Sejarah Indonesia - Chadilak, Ari (Yayasan Alpatih Harapan Semesta, 2025)
This study aims to explore the history, symbolic meaning, and socio-cultural transformation of the peci (traditional cap) as a crucial element of Islamic identity and nationalism in Indonesia. The peci serves not only as a religious head covering but has also undergone a shift in meaning, emerging as a political, national, and popular cultural symbol. The research adopts a historical qualitative approach using a literature review method, utilizing data from archives, historical documents, and scholarly articles published in accredited national and international journals. The research instrument involves thematic analysis that categorizes the peci’s meanings into religious, nationalist, and performative dimensions. The findings reveal that the peci has layered meanings since the colonial period, becoming a symbol of resistance and national identity, and is now used in various contexts ranging from religious rituals to contemporary performance art. These findings are supported by the analysis of fifteen reputable DOI-indexed journals, which demonstrate that the peci is a dynamic cultural artifact and a symbolic arena for negotiating identity in Indonesia’s social space.